Test of the Jump Service Spin in Volleyball - Ciro Alminni; Tiziana D'Isanto; Francesca D'Elia; Gaetano Altavilla (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
This pilot study aimed to test a procedure to evaluate the improvement of the performance in the short term between incoming and outgoing periods of the volleyball fundamental of the spin jump service by measuring accuracy and differential in the jump. The procedure was performed on a sample of 11 male players (amateur team), aged between 15 and 20 years. Data were collected at the beginning and the end of a four-week intensive training period and included mean and standard deviation of anthropometric data, reach to a hand, Vertec testing, and estimation of the training effect with percentages of improvement. The statistical analysis of the data was conducted with a T-test to verify the difference between the pre and post-workout. The significant difference was set with p<0.05. After four weeks of training, the jump increased by 3.45 cm. In the jump service with a choice of area, the training has produced a precision increase of 16%; while in the jump service in Zone 1, it produced an increase of 16%. Testing the spin service is useful because it enables monitoring performance, designing the training properly, and choosing the most effective training methodology. This test can be a fundamental tool for training and for identifying the best adaptations to be made to the training programme.